2012
DOI: 10.1179/1743278212y.0000000013
|View full text |Cite
|
Sign up to set email alerts
|

Monomers of lignin as corrosion inhibitors for mild steel: study of their behaviour by factorial experimental design

Abstract: This paper investigates the role of monomers of lignin on the corrosion inhibition of mild steel and their main and interaction effects on the corrosion parameters. A combination of statistical analysis and interaction contour plots has been employed to obtain an in depth understanding of the corrosion variables. Electrochemical tests were performed on three lignin monomers namely p-coumaric acid (CA), ferulic acid (FA) and hydroxybenzaldehyde (HB) on mild steel in near neutral solution. The CA and FA showed b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 28 publications
(54 reference statements)
0
6
0
Order By: Relevance
“…In acidic solution, the inhibition efficiency of lignin and its modifications for steel depend on the number of carboxy groups in the macromolecule [19], the inhibitor concentration, and the environmental factors [20]. In neutral aqueous solutions with Cl − , lignin monomers acted as mixed type inhibitors on steel corrosion [21] and the inhibitive performance of lignin derivatives depended on their functional groups [22]. Bishop et al [23] have confirmed that the –SO 3 and –OH groups present in LS can be adsorbed on a steel surface and generate an impermeable structure.…”
Section: Introductionmentioning
confidence: 99%
“…In acidic solution, the inhibition efficiency of lignin and its modifications for steel depend on the number of carboxy groups in the macromolecule [19], the inhibitor concentration, and the environmental factors [20]. In neutral aqueous solutions with Cl − , lignin monomers acted as mixed type inhibitors on steel corrosion [21] and the inhibitive performance of lignin derivatives depended on their functional groups [22]. Bishop et al [23] have confirmed that the –SO 3 and –OH groups present in LS can be adsorbed on a steel surface and generate an impermeable structure.…”
Section: Introductionmentioning
confidence: 99%
“…By studying the adsorption isotherm model and the corresponding formula, the corresponding adsorption parameters, such as the adsorption equilibrium constant and adsorption free energy, can be calculated to investigate the adsorption mechanism of this corrosion inhibitor. The values of the surface coverage (θ) are defined and calculated as IE/100 from the weight loss measurements using the following equation [41]: Several isothermal adsorption methods were matched by the experimental results, following the Langmuir adsorption isotherm model. The adsorption isotherm is as follows and the plot is shown in Figure 7.…”
Section: Resultsmentioning
confidence: 99%
“…The samples were taken out, washed, dried and accurately reweighed. The inhibition efficiency was calculated according to Equation (1) [41] IE false(%false) = (W0normalW) W0×100…”
Section: Materials and Experimental Methodsmentioning
confidence: 99%
“…The adsorption mechanism of organic compounds occurs either directly, on the basis of donoracceptor interactions between the relatively loosely bound electrons such as in anions and organic molecules and/or the heterocyclic compound which has lone pair electrons, or the p-electrons with the vacant d-orbitals of metallic iron atoms. Some parameters such as organic molecule size, number of functional groups, polarity that contribute to the formation of a strong bond or the rate of adsorption of inhibitor compounds onto the surface could affect the adsorption mechanism or inhibition action [59]. The Langmuir adsorption isotherm provides a simple mechanistic picture of the adsorption process and gives rise to a relatively simple mathematical expression.…”
Section: Adsorption Isothermmentioning
confidence: 99%